1994
DOI: 10.1111/j.1600-0528.1994.tb01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in toothbrushing and utilization of dental services in Finland

Abstract: Prevention and control of common dental diseases highly depends on individual behavior, and during the last decades, individuals have increasingly been required to take responsibility for their own oral health. In Finland the rate of toothbrushing and dental visits were first surveyed nationwide in 1971 by interviews with a sample of 1063 individuals, drawn to represent the total population aged 15 yr and over. At the time, 68% of the 829 dentulous interviewees claimed to brush at least once a day. Using anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
4
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 10 publications
6
12
4
4
Order By: Relevance
“…In our study, only 53.6% and 22% of patients reported a dental visit within the previous 6 months and previous 6-12 months, respectively, which was higher than the rate in the study done by Murtomaa et al (53%) (28). It seems that the present patients were never informed of the importance of regular dental examinations.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In our study, only 53.6% and 22% of patients reported a dental visit within the previous 6 months and previous 6-12 months, respectively, which was higher than the rate in the study done by Murtomaa et al (53%) (28). It seems that the present patients were never informed of the importance of regular dental examinations.…”
Section: Discussioncontrasting
confidence: 87%
“…The proportion of those who brushed more than twice daily (11.4%) was considerably lower than proportions reported by Karikoski (5,28). In a study of Finnish adults with diabetes, twice-daily brushing was reported by 50% of participants (12).…”
Section: Discussionmentioning
confidence: 70%
“…It is even less than what has been reported among the general public in Germany, Japan, New Zealand, the USA, and Poland [23], the UK [24] and Finland [25,26]. The effects of various dental curricula on these differences have also been emphasised [5,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported for the populations of Lithuania (Petersen et al, 2000) and China (Zhu et al, 2005). However, in most industrialized countries, the percentages of senior citizens claiming to use dental floss and brush teeth regularly or at least once a day were much higher (Chadwick et al; Christensen et al, 2003;Davidson et al, 1997;Murtomaa et al, 1994;Payne & Locker, 1992;Whelton et al, 2007). In the present study, as in all other relevant studies (Chadwick et al2011;Christensen et al,2003;Payne & Locker, 1992;Whelton et al, 2007) flossing frequency was much lower than brushing frequency probably because flossing is a more complex activity requiring more time and a certain degree of manual dexterity.…”
Section: Behavioral Parametersmentioning
confidence: 99%